Investigating the Implementation of Google Classroom to Improve Reading Comprehension: Advantage and Disadvantage - Lusi Susanti; Esti Junining; Hamamah Hamamah (Journal of Languages and Language Teaching, 2021)
When deciding to use the media, of course, the decision to use the media must be able to accept the advantages and disadvantages of the media. The advantages of a media used are expected to increase understanding in using the media, on the other hand, the disadvantages when using a media are expected to be minimized. This study aims to investigate the advantages and disadvantages as well as the effectiveness of using Google classroom media to improve students’ reading comprehension. The method used is descriptive qualitative study. The results of this study indicate that the use of Google Classroom media is effective in the learning process in ELT settings. This research presents the benefits of using this media in the learning process to improve reading comprehension. It can be accessed anytime and anywhere, flexible time, and a more innovative learning model (based on E-learning). Some of the benefits that can be obtained from using Google media, some shortcomings are encountered when using this media. Students must have a Google account, there is no face-to-face class, must be connected to the internet, and waste of internet financing.